2010
DOI: 10.1179/joc.2010.22.3.175
|View full text |Cite
|
Sign up to set email alerts
|

Serum Bactericidal Activity of Three Different Dosing Regimens of Colistin with Implications for Optimum Clinical Use

Abstract: Although colistin methanesulfonate (CMS) has been used extensively in critically ill patients infected with multidrug-resistant organisms, the optimum dosing regimen remains to be determined. Herein, we examined the pharmacokinetics of three different dosing regimens of CMS, 3 million units every 8 h (regimen A), 4.5 million units every 12 h (regimen B), 9 million units every 24 h (regimen C) and evaluated the bactericidal activity of serum containing various concentrations of colistin against Pseudomonas aeru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 9 publications
1
35
0
1
Order By: Relevance
“…Animal infection models have shown that the ratio of the area under the concentration-time curve for the free, unbound fraction of the drug (fAUC) to the MIC is the PK/PD index that is linked most strongly to an antibacterial effect, indicating the importance of achieving adequate time exposure to colistin across the day by administering the drug twice or three times a day (77,78). In contrast, however, several features of this drug, such as its prolonged half-life, its concentration-dependent killing, and a phenomenon known as "adaptive resistance" that has not been appreciated adequately (50,68,92,236), favor a once-daily dosing regimen, provided that such a scheme is not proven to be more nephrotoxic. Thus, a better understanding of the complex PK/PD features of colistin will be essential in devising dosing regimens with improved efficacy against CPE infections.…”
Section: Review Of Clinical Studiesmentioning
confidence: 99%
“…Animal infection models have shown that the ratio of the area under the concentration-time curve for the free, unbound fraction of the drug (fAUC) to the MIC is the PK/PD index that is linked most strongly to an antibacterial effect, indicating the importance of achieving adequate time exposure to colistin across the day by administering the drug twice or three times a day (77,78). In contrast, however, several features of this drug, such as its prolonged half-life, its concentration-dependent killing, and a phenomenon known as "adaptive resistance" that has not been appreciated adequately (50,68,92,236), favor a once-daily dosing regimen, provided that such a scheme is not proven to be more nephrotoxic. Thus, a better understanding of the complex PK/PD features of colistin will be essential in devising dosing regimens with improved efficacy against CPE infections.…”
Section: Review Of Clinical Studiesmentioning
confidence: 99%
“…These dosing regimens were previously found to result in tC max + SD 5.83+0.87, 2.98+0.27 and 3.34+0.35 mg/L; total tC min + SD 2.60+1.12, 2.01+0.47 and 1.63+0.23 mg/L; and tAUC 0-24 + SD 72.93+38.57, 60.71+12.0 and 50.18+10.74 mgÁh/L, respectively. 9 The Monte Carlo simulation was performed using the normal random number generator function of Excel (MS Office 2007) and the corresponding fC max and fAUC were calculated based on the 40% of unbound fraction of colistin in human serum. 8 The PK/PD PTA associated with a 2 log kill effect was calculated for each MIC and dosing regimen.…”
Section: Monte Carlo Simulations and Analysismentioning
confidence: 99%
“…A high proportion of clinician-selected dosing regimens result in sub-therapeutic colistin concentrations. [12,15,17,26,31,33] Of particular concern is a recent study showing that it is not possible to reach the modest target [2,43] colistin AUC/MIC of 60 in patients with creatinine clearances >70 ml/ min without exceeding the upper limit daily dose of 10 MU CMS recommended in the package insert. [17] …”
Section: Pharmacokineticpharmacodynamic Relationshipsmentioning
confidence: 99%
“…Peak concentrations of at least 4 mg/l (four times the MIC) were needed to eliminate P. aeruginosa in one study, but in critically ill patients this concentration was only reached with doses of 9 MU of CMS. [31] A recent in vitro study showed that the mutant prevention concentration (at which 90% of isolates tested were prevented from developing mutant strains) exceeds 128 mg/l, [32] a concentration not achievable with currently used doses. A high proportion of clinician-selected dosing regimens result in sub-therapeutic colistin concentrations.…”
Section: Pharmacokineticpharmacodynamic Relationshipsmentioning
confidence: 99%
See 1 more Smart Citation